OA. (3x+3)(5x-4)
OB. (3x+4)(5x-3)
C. (x+3)(15x-4)
OD. (x+4)(15x-3)
Answer:
B
Step-by-step explanation:
given the trinomial
15x² + 11x - 12
consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 15 × - 12 = - 180 and sum = + 11
the factors are + 20 and - 9 , since
+ 20 × - 9 = - 180 and + 20 - 9 = + 11
use these factors to split the x- term
15x² + 20x - 9x - 12 ( factor the first/second and third/fourth terms )
= 5x(3x + 4) - 3(3x + 4) ← factor out (3x + 4) from each term
= (3x + 4)(5x - 3)
56
60
Answer:
c
Step-by-step explanation: